A NONLOCAL FORMULATION OF THE DBAR FORMALISM AND BOUNDARY VALUE PROBLEMS IN TWO DIMENSIONS - PINOTSIS, D. A. (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
We present an approach for solving a large class of boundary value problems for non-homogeneous elliptic Partial Differential Equations. We also present a nonlocal formulation of an important problem in complex analysis, the Dbar problem. As particular applications of our approach, we solve boundary value problems for the non homogeneous biharmonic as well as the equations governing creeping flow.